Music, Memory and Repression in Hitchcock’s Vertigo (1958) - Christophe Gelly (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2021)
The musical dimension has always been presented by critics as an essential part of Hitchcock’s narrative technique, with a view to showing how music works at emphasizing the suspense situations in his thrillers. This article tries to expand upon the complex, shifting role of music in the Hitchcock corpus by focusing on the case of Vertigo (1958), as a film which clearly makes use of musical references and repetitions as subjective landmarks pointing to the spectator’s access to Scottie’s psyche—hence as somewhat detached from the suspense-driven dramatic situations proper. Music can be related to the main character’s reconstruction of Madeleine’s image through Judy, but also appears as a possible expression of his hesitations and of the repression of this desire to recreate his dead lover. As such, it constitutes a potentially self-conscious part of the filmic discourse focused not only on the expression of characters’ feelings but also on the necessary distance with them.